2018
DOI: 10.17221/383/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Juices enriched with phenolic extracts from grapes

Abstract: The chemical composition of organic compounds in the extractable organic matter of propolis collected from the Baha region of Saudi Arabia was investigated. The propolis samples were extracted with methanol followed by column chromatography and collected in fractions (15 ml), then analysed by gas chromatography-mass spectrometry (GC-MS). Samples were injected with and without derivatization using BSTFA simultaneously. The results showed that a total of 61 chemical compounds were characterized and identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Altunkaya et al ( 2013 ) observed in their study when pomegranate peel extract (500 mg/100 mL) was added to apple juice, the relative level of free radicals dropped by 5% while TPC was amplified by 19% in contrast to the control. Kulichová et al ( 2018 ) have found that TPC, FRAP, DPPH, catechin, and epicatechin concentrations improved by roughly 70, 140, 190, 50, and 160 percent, compared to non-fortified juices when an extract of grape press oil cake was added (50 mg/100 mL). The same extract was employed by the authors to fortify apple juice and got comparable outcomes using the procedures mentioned above.…”
Section: Solutions For Increasing the Usage Of Fbpsmentioning
confidence: 99%
“…Altunkaya et al ( 2013 ) observed in their study when pomegranate peel extract (500 mg/100 mL) was added to apple juice, the relative level of free radicals dropped by 5% while TPC was amplified by 19% in contrast to the control. Kulichová et al ( 2018 ) have found that TPC, FRAP, DPPH, catechin, and epicatechin concentrations improved by roughly 70, 140, 190, 50, and 160 percent, compared to non-fortified juices when an extract of grape press oil cake was added (50 mg/100 mL). The same extract was employed by the authors to fortify apple juice and got comparable outcomes using the procedures mentioned above.…”
Section: Solutions For Increasing the Usage Of Fbpsmentioning
confidence: 99%
“…Adiamo et al [65] showed that the addition of orange peel and pulp phenolic extracts in carrot juice enhanced its phenolic content and antioxidant activity; however, higher amounts of phenolic and antioxidant activity were obtained in juice containing peel phenolic extract. Kulichová et al [66] evaluated the impact of phenolic extracts from oil cake of white grapes in apple and grape juices, concluding that the juice with 1 g/L of extract increased in antioxidant capacity and total polyphenol content two-fold [66]. Larrosa et al [67] reported that inserting an phenolic-enriched extract from blanched artichoke by-product in a tomato juice resulted in higher antioxidant activity (measured by in vitro methods) and, consequently, a longer shelf life for the tomato juice.…”
Section: Antioxidant Extractsmentioning
confidence: 99%
“…Nowadays, emerging studies on effect of isolated fractions rich in biologically active compounds on specific and targeted biochemical functions and their biological role are being carried out and addressed in perspective of the application and uses in nutraceutical and functional foods (Andrew & Izzo, ; Daliu, Santini, & Novellino, ; Santini et al, ; Santini & Novellino, ; Santini, Novellino, Armini, & Ritieni, ; Santini, Tenore, & Novellino, ; Speranza et al, ). In this context, several works have studied the use of bioactive components or antioxidant extracts as additional ingredient in fruit‐based juice and their related implemented properties (Ivanišová et al, ; Kulichová et al, ; Tarazona‐Díaz, Martínez‐Sánchez, & Aguayo, ) or new juice formulation (Lachowicz & Oszmiański, ). Emerging direction was the addition of active ingredient from food wastes in formulation of fruit‐based juice (Afkhami, Goli, & Keramat, ; López‐Nicolás, González‐Bermúdez, Ros‐Berruezo, & Frontela‐Saseta, ; Martinez, Valderrama, Moreno, & De Bruijn, ).…”
Section: Effect Of Processing Techniques On Antioxidants In Food Matrmentioning
confidence: 99%